An evaluation of EC2 rules for design of compression lap joints. (February 2016) - Cairns, John
Abstract: This paper presents an evaluation of EC2 rules for design of compression lapped joints based around a database of approximately 150 individual test results reported in the literature. A comparison is provided between tension and compression laps, and a review of semi-empirical and empirical expressions reported in the literature is presented. Compared to laps of bars in tension, the influence of minimum concrete cover on compression lap strength is low or negligible, but the influence of transverse reinforcement is stronger. The performance criteria for lapped joints are discussed, and a difference noted between compression and tension laps. The evaluation has been carried out by first determining the lap length required by EC2 to develop the design strength of a bar, and the strength of that lap then estimated using three different semi-empirical expressions each derived from part of the database. The outcome shows that EC2 procedures provide a greater margin of safety for compression laps than for tension laps. The margin of safety against failure of compression laps designed in accordance with EC2 is found to be broadly consistent with expectations for a concrete cover equal to one bar diameter, but reduces at larger cover/bar diameter ratios. Consequently it is recommended that for compression laps coefficient α2 be independent of cover ratio and set to 1.0.